A high efficiency Stirling/pulse tube hybrid cryocooler operating at 35 K/85 K. (July 2019) - Liu, Biqiang; Jiang, Zhenhua; Ying, Kongkuai; Zhu, Haifeng; Liu, Shaoshuai; Wen, Fengshuo; Wu, Yinong; Dong, Deping
Highlights: A high efficiency Stirling/pulse tube hybrid cryocooler operating at 35 K/85 K is reported. A schematic diagram and the photograph of the novel hybrid structure is involved. The cooling capacity of 1.16 W@35 K & 7.25 W@85 K with input power of 234.6 W can be obtained. Abstract: Stirling/Pulse tube hybrid cryocooler (SPC) combines the high efficiency feature of Stirling cryocooler and the high reliability feature of pulse tube cryocooler, which is attractive for space applications with tight requirements on the cryocooler. A SPC has been designed and manufactured in our laboratory. The SPC obtains cooling capacities of 1.06 W at 30 K plus 4.46 W at 80 K with the input electric power of 261.2 W and 1.16 W at 35 K plus 7.25 W at 85 K with the input electric power of 234.6 W (including displacer input power). The operating frequency is 40 Hz and the heat rejection temperature is 315 K.